Multi-objective optimization of energy absorbing behavior of foam-filled hybrid composite tubes. (1st January 2022) - Meriç, Dursun; Gedikli, Hasan
Abstract: The aim of this study is to investigate the energy-absorbing behaviors of hybrid composite tubes under static load and their multi-objective optimization. For this purpose, energy-absorbing behaviors of single (S_Al, S_St, S_C) and double (D_Al-St, D_Al-C, D_St-C) tubes made of Al 6063, St 52, and CFRP are numerically investigated. Static compression tests are performed for single and double tubes and modeled with the finite element method. Besides, Foam 1 (500 kg / m 3 ), Foam 2 (750 kg / m 3 ) and Foam 3 (1000 kg / m 3 ) aluminum foam fillers with different densities are used in single and double tubes. In foam-filled single and double tubes, wall thicknesses were (1–4 mm) and foam densities were (500–1500 kg / m 3 ); multi-objective optimization studies (MOO) were carried out in order to obtain the lowest peak force, highest specific energy absorption (SEA), and crash force efficiency (CFE). As a result of the optimization studies, it has been observed that it is possible to increase the absorbed energy values without sacrificing SEA values in double tubes.